1982
DOI: 10.1111/j.1476-5381.1982.tb09226.x
|View full text |Cite
|
Sign up to set email alerts
|

Lidoflazine in the Early Stages of Acute Myocardial Ischaemia

Abstract: Gl 1XW1 Pretreatment of anaesthetized rats with intravenously administered lidoflazine (an antianginal agent) reduced the incidence and severity of ventricular arrhythmias which resulted from acute coronary artery ligation. Ventricular fibrillation was completely prevented by doses of 50 pg/kg and 2 mg/kg and no animal so treated died (contrast 50% incidence of fibrillation in the controls and 30% mortality). 2 In anaesthetized greyhound dogs, lidoflazine (2 mg/kg) administration resulted in transient reductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1986
1986
1997
1997

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…Previous studies with the few existing nucleoside transport inhibitors such as dipyridamole (Wainwright & Parratt, 1988) and lidoflazine (Coker et al, 1982) have indeed shown protection against ventricular arrhythmias during coronary occlusion in dogs. Furthermore, dipyridamole (Blumenthal et al, 1981), lidoflazine (Flameng et al, 1981), mioflazine (Wood et al, 1985) and dilazep (Gupta et al, 1989) have all been shown to reduce infarct size and/or improve functional recovery after myocardial ischaemia in canine hearts.…”
Section: Introductionmentioning
confidence: 87%
“…Previous studies with the few existing nucleoside transport inhibitors such as dipyridamole (Wainwright & Parratt, 1988) and lidoflazine (Coker et al, 1982) have indeed shown protection against ventricular arrhythmias during coronary occlusion in dogs. Furthermore, dipyridamole (Blumenthal et al, 1981), lidoflazine (Flameng et al, 1981), mioflazine (Wood et al, 1985) and dilazep (Gupta et al, 1989) have all been shown to reduce infarct size and/or improve functional recovery after myocardial ischaemia in canine hearts.…”
Section: Introductionmentioning
confidence: 87%
“…Anti-arrhythmic actions have been reported in a coronary occlusion model in dogs for dipyridamole [65] and lidoflazine [66] and in pigs for R 75 231 [67]. In the latter study, 9 out of 10 control animals died from ventricular fibrillation, while 8 out of 10 survived when pretreated with R 75 231.…”
Section: Arrhythmiasmentioning
confidence: 89%
“…The aspirin studies, conducted almost entirely in anesthetized dogs [32], suggest that the selective inhibition of thromboxane (and the "sparing" of prostacyclin) is the most likely explanation of the antiarrhythmic effect of lower doses of aspirin (e.g., 1 mg/ kg). What is of particular interest in all these experiments is that the selective inhibition of thromboxane release leads particularly to suppression of ventricular fibrillation that occurs following reperfusion.…”
Section: Importance Of "'Sparing" Prostacyclin Under Conditions Of Mymentioning
confidence: 99%